Is prescribing medicine with generic formula the practical solution to control price? - Jameel, Maria; Rehna, Tasnim (Journal of the Pakistan Medical Association, 2023)
The Drug Regulatory Authority of Pakistan (DRAP) recently sent a letter to all provincial health departments advising their health professionals to prescribe a drug’s generic formula instead of its generic name. The decision was taken to control the price of drugs and break the nexus between pharmaceutical companies and doctors 1who prescribe the company-promoted branded medication. The Prime Minister’s Performance delivery unit took this initiative in response to several complaints received regarding doctors prescribing brand names of expensive medicines despite the cheaper available alternatives in the market. The matter rose to prominence, particularly during the pandemic of COVID-19 when pharmaceutical companies suddenly overpriced different medicines crucial for the sufferers of the pandemic. People started complaining and questioning on the agreement between the doctors and pharmaceutical companies regarding this malpractice of prescribing drugs. The irresponsible attitude of using medicines by the consumers and unnecessary prescription of drugs by doctors has been a global problem,,2 moreover, it has been observed that healthcare costs in general and drug costs are rising everywhere, largely because of new medicines. But the overpricing in last years was due to the DRAP policies.3 The whole idea of using the generic formula on prescription is not the only way to control medicine’s price. Still it involves other serious issues, such as an agreement between pharmacy and pharmaceutical companies to give their brand when the doctor does not prescribe the drug by name. The suggestion is not workable because the doctor decides a medicine to be given to a patient based on his disease, needs and condition. The doctor selects a particular brand based on his experience and confidence in that brand. So, his expertise and brand reputation play an essential role in his prescription decisions. Moreover, there is a shortage of qualified, trained pharmacists so implementing the suggestion could be harmful to patients’ health because it would encourage substandard drugs.4 The government can control the price by using more practical andless uncomplicated strategies. The high cost and inaccessibility of essential medicine across Pakistan are related to weak quality assurance regulations, poor affordability, and irrational use.3 One of the critical solutions to the problem of price control is to set the price of generic brands in respect to the average price of the similar generic drugs available in the market. —Continue